Impact of baseline left ventricular ejection fraction on long-term outcomes in cardiac contractility modulation therapy: devices - Yücel, Gökhan; Fastner, Christian; Hetjens, Svetlana; Toepel, Matthias; Schmiel, Gereon; Yazdani, Babak; Husain-Syed, Faeq; Liebe, Volker; Rudic, Boris; Akın, Ibrahim; Borggrefe, Martin; Kuschyk, Jürgen (Pacing and clinical electrophysiology, 2022)
Background Cardiac contractility modulation (CCM), being reserved for patients with symptomatic chronic heart failure (HF) and narrow QRS complex under guideline directed medical therapy, can recover initially reduced left ventricular ejection fraction (LVEF); however, the influence of pre-implantation LVEF on long-term outcomes is not fully understood. This study aimed to compare the effects of lower and higher preimplantation LVEF on long-term outcomes in CCM-therapy. Methods One-hundred seventy-two patients from our single-centre registry were retrospectively included (2002-2019). Follow-up data were collected up to 5 years after implantation. Patients were divided into Group 1 (baseline LVEF≤ 30%) and Group 2 (≥ 31%). Both groups were compared based on differences in survival, echocardiographic- and clinical parameters including LVEF, tricuspid annular plane systolic excursion (TAPSE), NYHA class or Minnesota living with heart failure questionnaire-score (MLWHFQ). Results 11% of the patients did have a LVEF ≥31%. Mean LVEF ± SD for both groups were 21.98 ± 5.4 versus 35.2 ± 3.7%, respectively. MLWHFQ (47 ± 21.2 vs. 42±21.4) and mean peak oxygen consumption (VO2, 13.6 ± 4.1 vs. 12.7 ± 2.8 ml/kg/min) were comparable between both groups. LVEF-grouping did not influence survival. Lower baseline LVEF resulted in significantly better recovery of echocardiographic parameters such as LVEF and TAPSE. Irrespective from baseline LVEF, both groups showed nearly comparable improvements for clinical parameters like NYHA-class and MLWHFQ. Conclusion Long-term biventricular systolic recovery potential in CCM-therapy might be better for preimplantation LVEF values ≤30%, whereas clinical parameters such as NYHA-class can improve irrespective from baseline LVEF.